Intramuscular sex steroid hormones are associated with skeletal muscle strength and power in women with different hormonal status. Issue 2 (20th January 2015) - Pöllänen, Eija; Kangas, Reeta; Horttanainen, Mia; Niskala, Paula; Kaprio, Jaakko; Butler‐Browne, Gillian; Mouly, Vincent; Sipilä, Sarianna; Kovanen, Vuokko
Summary Estrogen (E2)‐responsive peripheral tissues, such as skeletal muscle, may suffer from hormone deficiency after menopause potentially contributing to the aging of muscle. However, recently E2 was shown to be synthesized by muscle and its systemic and intramuscular hormone levels are unequal. The objective of the study was to examine the association between intramuscular steroid hormones and muscle characteristics in premenopausal women (n = 8) and in postmenopausal monozygotic twin sister pairs (n = 16 co‐twins from eight pairs) discordant for the use of E2‐based hormone replacement. Isometric skeletal muscle strength was assessed by measuring knee extension strength. Explosive lower body muscle power was assessed as vertical jump height. Due to sequential nature of enzymatic conversion of biologically inactive dehydroepiandrosterone (DHEA) to testosterone (T) and subsequently to E2 or dihydrotestosterone (DHT), separate linear regression models were used to estimate the association of each hormone with muscle characteristics. Intramuscular E2, T, DHT, and DHEA proved to be significant, independent predictors of strength and power explaining 59–64% of the variation in knee extension strength and 80–83% of the variation of vertical jumping height in women (P < 0.005 for all models). The models were adjusted for age, systemic E2, and total body fat mass. The statistics used took into account the lack of statistical independence of twin sisters. Furthermore, muscle cells were shown to take up and actively synthesize hormones. Present study suggests intramuscular sex steroids to associate with strength and power regulation in female muscle providing novel insight to the field of muscle aging.